Synthetic Strategies Toward the Decalin Motif of Maklamicin and Related Spirotetronates - Lacoske, Michelle H. (Org Chem Front, 2015)
Herein we describe a scalable approach to the decalin moiety of maklamicin. Key to the synthesis is an intramolecular Diels-Alder (IMDA) reaction that proceeds via an endo-axial transition state to generate the desired stereochemistry. We explored the diastereoselectivity of the IMDA reaction as a function of both chiral catalysis and acyclic precursor stereochemistry.